2017
DOI: 10.1371/journal.pone.0187158
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width as a novel marker for predicting high-risk from upper gastro-intestinal bleeding patients

Abstract: BackgroundIn upper gastrointestinal bleeding (UGIB) patients, early risk stratification allows appropriate therapy that may be helpful for reducing morbidity and mortality.Objectivesto evaluate the efficacy of red-cell distribution width (RDW) for prediction of high-risk in UGIB patients.MethodsWe conducted a clinical retrospective observational study based on data for UGIB patients from 2012 to 2013. The primary outcome was the high-risk UGIB, defined as those who required urgent intervention and/or 30-days m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…In our study, death due to gastrointestinal cancer was significantly associated with RDW. Gastrointestinal hemorrhage is commonly seen in diseases of digestive organs, which potentially could stimulate erythropoietin (EPO) production and provoke anisocytosis 19 . However, the relationship was not completely attenuated after adjustment for anaemia, which might suggest that gastrointestinal bleeding is not the only reason for the increased RDW.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, death due to gastrointestinal cancer was significantly associated with RDW. Gastrointestinal hemorrhage is commonly seen in diseases of digestive organs, which potentially could stimulate erythropoietin (EPO) production and provoke anisocytosis 19 . However, the relationship was not completely attenuated after adjustment for anaemia, which might suggest that gastrointestinal bleeding is not the only reason for the increased RDW.…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration of liver function and cirrhosis on its own makes surgery difficult and may increase the risk of bleeding, associated with a thrombotic state [ 47 , 48 ]. In addition, recent studies reported that elevated RDW may be associated with bleeding risk [ 49 ]. The suppression of erythrocyte maturation by inflammatory cytokines causes anisocytosis and abnormal erythropoietin function, which is associated with anemia, thrombotic state [ 50 ], and hemorrhagic tendency [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies reported that elevated RDW may be associated with bleeding risk [ 49 ]. The suppression of erythrocyte maturation by inflammatory cytokines causes anisocytosis and abnormal erythropoietin function, which is associated with anemia, thrombotic state [ 50 ], and hemorrhagic tendency [ 49 , 51 ]. In this study, there was a significant difference in RDW values according to the PNI cut-off value; this may have a significant correlation with the findings of the study.…”
Section: Discussionmentioning
confidence: 99%
“…[ [14][15][16] The mechanism by which RDW increases is not yet clear, but it has been reported to be associated with anemia, in ammatory responses and oxidative stress. [43] Increased RDW is a sign of a nutritional de cit, such as a de ciency of iron, folic acid, or vitamins B-12, which may indicate macrocytic anemia and may increase blood transfusion requirements during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that RDW is correlated with bleeding risk and transfusion for some diseases and procedures. [14][15][16] However, there are few studies on the association between preoperative RDW and intraoperative transfusion in LT. Therefore, in this study, we evaluated the association between preoperative RDW and intraoperative blood transfusion in patients who underwent living donor liver transplantation (LDLT).…”
Section: Introductionmentioning
confidence: 99%